Delayed chylopericardium after radical surgery for esophageal cancer: a case report - Yang, Pengjie; Han, Rui; Zhu, Benben; Wu, Yu; Han, Bater (Frontiers in Oncology, 2023)
Background Postoperative chylpericardiumChylopericardium is a rare clinical disease that often manifests as chest tightness, shortness of breathdyspnea, and other symptoms of pericardial tamponade. The etiological spectrum of chylopericardium is complex, but the disease is mainly idiopathic. Chylopericardium caused by thoracic surgery is rarely reported, both at home and abroad. Case summary We report a case of a 65-year-old male patient who developed chylopericardium after thoracoabdominal combined incision and partial esophagogastric anastomosis plus lymph node dissection for 1 month. After pericardiocentesis and drainage, low-fat enteral nutrition, and parenteral nutrition, the patient was cured. Based on this case, this article reviews the literature on the diagnosis and treatment of chylopericardium after thoracic surgery. Conclusion In conclusion, thoracic surgery (excluding cardiac surgery) can cause delayed chylopericardium. This condition is rarely reported in China, and only a few cases have been reported abroad. Thus, the diagnosis is likely to be missed or misdiagnosed. Early diagnosis and treatment are important to reduce patient discomfort as much as possible.